A high performance solid state transformer for an efficient electric grid application: Design and analysis for advanced nanocrystalline core material. (2021) - Gupta, Eva; Kumar Sinha, Sanjay; Kumar Vates, Umesh; Chavan, Sachin S.
Abstract: The single-phase medium and high frequency (MF/ HF) solid state transformer (SST) design is proposed as an alternative solution to fulfill the demand of high power applications. The traditional core material is replaced with high performance nanocrystalline materials resulting in an optimized flux density, and thus the maximized efficiency of high frequency SSTs is achieved through the transfer of optimum power. An interactive MATLAB program is developed to study the various parameters of the SSTs, such as the evaluation of some core materials through their magnetic characterization. The efficacy of the present investigation is established with the published data sets and a new material is proposed herewith for future applications in electrical power grids to meet the requirements of clean, green, and safe transmission of electric power.